Australian broadcast journalism - Phillips, Gail (Oxford University Press, 2006)
Australian Broadcast Journalism is a pratical guide to broadcast journalism. The text introduces students to broadcast journalism by exposing them to the thoughts and experiences of practising journalists across all the broadcast media--radio, television and the Web. It focuses on the skills journalists need to succeed and looks at how these skills are applied in the different broadcast media